HIGHS AND LOWS IN THE RELATIONSHIP BETWEEN HAMKA AND MUAHAMMADIYAH DURING THE PERIOD OF GUIDED DEMOCRACY - Akmal, Akmal; Abdurakhman, Abdurakhman (International Review of Humanities Studies, 2019)
Following the dissolution of Masyumi in 1960, the political climate was rather unfriendly for the Islamic movement in Indonesia. Since 1959, Muhammadiyah had given up its special membership status in Masyumi, while some of its administrators pursued political careers elsewhere. Muhammadiyah maintained good relations with Soekarno, notably after Soekarno’s speech in Muhammadiyah’s 35th National Congress in 1962. Hamka, a devoted member of Muhammadiyah, was stuck in a rather unique position due to this progress of events. This study aims to describe the highs and lows of the relationships between Hamka and Muhammadiyah during the Guided Democracy era (1959-1966). Literature study will be conducted by examining official Muhammadiyah documents, Soekarno’s speeches, Hamka’s writings and other materials available. Evidently, at one point, Muhammadiyah gave Soekarno the title of ‘The Faithful Member’ (Anggota Setia) and ‘The Great Protector’ (Pengayom Agung) of Muhammadiyah, and the Muhammadiyah University awarded him with the title of honorary doctorate in the Philosophy of Tawheed Science field. Hamka then launched harsh criticisms to Muhammadiyah regarding its attitude and closeness towards Soekarno which he considered to be rather unnatural. Nevertheless, Muhammadiyah never revised its actions, while Hamka continued to be one of Muhammadiyah’s lifelong devoted member.